PRACTICAL COMPONENT IN THE PROCESS OF PROFESSIONAL TRAINING OF THE SOCIAL SPHERE SPECIALISTS - Vira Korniat (Borys Grinchenko Kyiv Metropolitan University, 2022)
The article analyzes and characterizes the peculiarities of the organization of practice in the process of professional training of social work specialists in higher education institutions. It is determined that the process of professional training of any specialist is a reflection of changes and changes in society. High-quality professional training of social specialists also contributes to the establishment of the profession itself, and the competence of the specialist affects the effectiveness of social work. The essence of practice as the main component of professionalism, personal and professional growth of the future specialist in the social sphere is considered. Difficulties in organizing the internship are emphasized (lack of a social worker as a specialist or lack of appropriate professional education, unclear definition of his professional responsibilities, inconsistency of the general activities of the social institution and the content of the social worker's professional activities, unwillingness to hire students). Forms and methods of working with students at the stage of choosing the base of practice (meetings-presentations in the institution councils, independent work, volunteering) are offered. The basic principles of organization of practice are defined and characterized (feedback of theoretical training and practice, consistency, continuity, dynamism, field functionality, perspective, freedom of choice, cooperation). Further prospects of research of use of various organizational forms for formation of professional competence of experts of social sphere, in particular its practical component are offered.